An Experimental Investigation of Steel Fiber Reinforcement in High Performance Concrete - V.C.Shajan , Dr. N.Nalanth, Y.Abisha , S.Sunil Kumar (International Journal of Advanced Science and Technology, 2020)
The excessive use of natural resources can be minimized by using eco friendly waste materials. The construction and demolition wastes can be used as recycled aggregates by replacing natural coarse as well as fine aggregates, so that the depletion of natural resources can be reduced. The construction of concrete structures without making vibration was carried out in past also but their strength and consistent quality is low. In order to overcome these disadvantages self compacted concrete with high performance was developed. This review study is based on the types of recycled aggregate materials used, series of mixes done by using recycled concrete aggregate, type of admixtures used etc. The super plasticizers used for improving certain properties are also discussed from various paper studied it came to know that when 100% of natural concrete aggregate replaced with recycled concrete aggregate compressive strength of  39 Mpa is achieved [5].